2012
DOI: 10.3390/ijms13021951
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Heterogeneity: Mechanisms and Bases for a Reliable Application of Molecular Marker Design

Abstract: Tumor heterogeneity is a confusing finding in the assessment of neoplasms, potentially resulting in inaccurate diagnostic, prognostic and predictive tests. This tumor heterogeneity is not always a random and unpredictable phenomenon, whose knowledge helps designing better tests. The biologic reasons for this intratumoral heterogeneity would then be important to understand both the natural history of neoplasms and the selection of test samples for reliable analysis. The main factors contributing to intratumoral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
105
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(113 citation statements)
references
References 307 publications
(459 reference statements)
1
105
0
3
Order By: Relevance
“…An extensive range of miR-146a expression levels observed in primary tumor tissues in the present study may support this hypothesis. Primary tumors are composed of cell clones with different invasive potentials (35). It was demonstrated that the pattern of miRNA expression varied between cultured SKOV-3 and OVCAR-3 cell lines and was associated with invasiveness (36).…”
Section: Discussionmentioning
confidence: 99%
“…An extensive range of miR-146a expression levels observed in primary tumor tissues in the present study may support this hypothesis. Primary tumors are composed of cell clones with different invasive potentials (35). It was demonstrated that the pattern of miRNA expression varied between cultured SKOV-3 and OVCAR-3 cell lines and was associated with invasiveness (36).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, rare subclones not detected by MS-MLPA may have the capacity to become driver events (and vice versa) as environmental selection pressures change during tumor growth and therapeutic intervention. 24 In summary, we have demonstrated that clonal epigenetic heterogeneity is present within most primary breast carcinomas and can lead to aberrant methylation status calling by MS-MLPA, indicating that analysis of a single random sample may not be representative of the whole tumor, which may hamper epigenetic biomarker discovery and validation. Intertumor heterogeneity was nevertheless more pronounced than intratumor heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…The features in common with stem cells are: indefinite self-replication, asymmetric cell division, and resistance to toxic agents, owing, in part, to elevated expression of ABC transporters [199,200,201]. In addition, they are also characterized by genetic instability (chromosomal and microsatellite), changes of chromatin, transcription and epigenetics, mobilization of cellular resources, and modified microenvironment interactions (tumour cells, stromal cells, extracellular, endothelium) [202]. Both paradigms of tumour propagation are likely to exist in human cancer but only the CSC model is hierarchical.…”
Section: Cancer Stem Cells and Apoptosismentioning
confidence: 99%
“…This theory continued to evolve, and the isolation of four different tumour subpopulations from a single breast cancer in a mouse was reported in the decade of the 80s [204]. Tumour heterogeneity is reflected in different phenotypic aspects such as cell morphology, gene expression, metabolism, motility and proliferation, immunogenic, angiogenic and metastatic potential [202]. Molecular characterization of CSCs is necessary to develop a targeted therapy (Table 6).…”
Section: Cancer Stem Cells and Apoptosismentioning
confidence: 99%